Does a toothpaste containing blue covarine have any effect on bleached teeth? An in vitro, randomized and blinded study - Bortolatto, Janaina Freitas [UNESP]; Rached Dantas, Andrea Abi [UNESP]; Roncolato, Avery [UNESP]; Merchan, Hugo [UNESP]; Floros, Michael Christopher; Kuga, Milton Carlos [UNESP]; Oliveira Junior, Osmir Batista de [UNESP] (Sociedade Brasileira De Pesquisa Odontologica, 2016)
The objective of this study was to analyze the effect of bleaching toothpastes, both conventional and those containing the new whitening agent Blue Covarine, on teeth previously bleached by conventional techniques (in-office and at-home). Squared bovine enamel/dentin blocks (6.0 x 6.0 x 2.0 mm) were randomly distributed in 6 groups (n = 15), according to the technique used to bleach them (in-office: HP35%; at-home: PC10%) and the type of bleaching toothpaste (none: control; Blue Covarine containing: BC; and without Blue Covarine: NBC). Experimental groups denominated HP35%, HP35% BC and HP35% NBC received in-office tooth bleaching before toothbrushing, and groups PC10%, PC10% BC and PC10% NBC were subjected to at-home tooth bleaching prior to toothbrushing. After bleaching treatment, groups HP35% BC, PC10% BC, HP35% NBC and PC10% NBC underwent daily tooth brushing in a brushing machine for 3 minutes (150 strokes/min, with a load of 375 g). Tooth color alteration was measured by reflectance spectroscopy (Vita EasyShade, Vident, Brea, CA, USA) at: T0 (baseline) - after in-office or at-home bleaching treatment; T1 - immediately after tooth brushing; T2 - 7 days and T3 - 14 days after tooth brushing. Data was analyzed by repeated measures mixed ANOVA and the Bonferroni post hoc test, with a significance level of 5%. Statistically significant differences were found between different experimental groups, evaluation times and for the interaction between them (p < 0.001). Tooth brushing using either bleaching toothpaste (conventional or with Blue Covarine) showed no color alteration on teeth previously bleached by in-office and at-home tooth bleaching. The use of bleaching toothpastes on previously bleached teeth did not produce a color alteration.
Keywords: Tooth Bleaching; Bleaching Agents; Denture Cleansers; Dentifrices